Plate-girder railway bridges - Fitzmaurice, Maurice, 1861- (E. & F.N. Spon, 1895)
The great majority of bridges on a line of railway are short-span plate-girder bridges. This book is intended to help those young engineers who, joining an engineers office for the first time, find themselves engaged in this class of work.